Hungary : Third Review Under the Stand-By Arrangement, Requests for Extension of the Arrangement, Rephasing of Purchases, and Modification of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Third Review Under the Stand-By Arrangement for Hungary. The end-June 2009 quantitative performance criteria, as well as the structural benchmark related to government lending to banks, were all met. The end-June indicative target on central government debt (excluding official financing) was not met for technical reasons. The key objectives of the program remain to improve fiscal sustainability and preserve financial stability. The macroeconomic outlook for 2009-10 has changed only modestly since the second review, reflecting in part the stabilization of the global outlook.